Urticaria multiforme in a 3-year-old child and review of the literature. - Abelha, L.; Sousa Fernandes, S.; Bonifazi, E.; Costa Azevedo, A. (European Journal of Pediatric Dermatology, 2025)
Urticaria multiforme is a variant of parainfectious urticaria characterized by annular aspects, ecchymotic sequelae, acral edema without pitting. These aspects may give rise to some problems of differential diagnosis with other conditions, especially erythema multiforme and neonatal hemorrhagic edema. In literature it is most often described with the questionable name of urticaria multiforme, but also with other terms such as annular, giant, ecchymotic urticaria that emphasize its different morphological aspects. A clinical case in a 3-year-old child was described and a complete review of the literature was performed.